Pengaruh Temperatur Kondensasi terhadap Kinerja Siklus Rankine Organik yang Menggunakan R245fa, R600a, R1234yf, dan R1234ze - Dwinanto, Matheus (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
The organic Rankine cycle (ORC) is an unconventional technology and has been widely used to conversion of thermal energy at low temperatures into electrical energy on a small scale. For this reason, the use of more environmentally friendly hydrocarbons and hydrofluoroolefins has become a demand and a central issue in the future. This paper presents a performance study of using R600a, R1234yf and R1234ze as drop-in replacement to R245fa in an ORC system. The system performance is based on the variation of the condensation temperature using Genetron Properties software with the evaporation temperature being held constant. The important quantities analyzed are mass flow rate, pumping power, heat absorption, heat rejected, turbine outlet temperature, turbine outlet superheat temperature, turbine pressure ratio, and thermal efficiency. The results show that the condensation temperature is very influential on system performance. It is not easy to determine the optimal performance for each working fluid used in the system independently so that the cycle simulation approach with a thermodynamic model while comparing the three working fluids with R245fa is the most common way. The results of this study indicate that the studied hydrocarbons and hydrofluoroolefins working fluid candidates have the same thermal efficiency as R245fa.